Feresa attenuata Gray 1874 ... - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
27. Pygmy Killer Whale Feresa attenuata French: Orque pygmée / German: Zwergschwertwal / Spanish: Orca pigmea Other common names: Slender Blackfish, Slender Pilot Whale Taxonomy. [leresa attenuata Gray, 1874, “South Seas.” This species is monotypic. Distribution. Cosmopolitan tropical and subtropical distribution between ¢.40° N and ¢.35° S, including the Gulfof Mexico and Arabian Sea. Descriptive notes. Total length 210- 260 cm; weight up to 225 kg. Neonates are ¢.80 cm long and weigh 15-20 kg. Male Pygmy Killer Whales may be slightly larger than females. The Pygmy Killer Whale has moderately robust body that tapers posteriorly into shallow tailstock. Head is bulbous and rounded, with no visible beak, and flippers are slender and slightly curved, with rounded tips. Dorsalfin, positioned about halfway along body, is tall and falcate. The Pygmy Killer Whale has dark-gray to black skin, with dark, narrow dorsal cape that dips below dorsal fin, contrasting with slightly paler gray flanks. Lips may be pale gray ... : Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Delphinidae, pp. 410-526 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on pages 518-519, DOI: 10.5281/zenodo.6610922 ...